Polar gigantism and remarkable taxonomic longevity in new palaeoscolecid worms from the Late Ordovician Tafilalt Lagerstätte of Morocco - García-Bellido, D.C.; Gutiérrez-Marco, J.C. (Historical Biology, 2023)
The Late Ordovician Tafilalt Biota of the Moroccan Anti-Atlas includes a diverse range of soft-bodied organisms, including palaeoscolecids, paropsonemid eldonioids, graptolites and cheloniellid arthropods, as well as a rich assemblage of mineralised taxa, among them conulariids, trilobites and echinoderms, often found as articulated skeletons. The new fossil locality, not far from the original Bou Nemrou site, has produced two new palaeoscolecid taxa, the new genus and species Anguiscolex africanus and the new species Wronascolex superstes. They are preserved as compression fossils in fine-grained mudstones, where the original phosphatic sclerites have been diagenetically substituted by pyrite and later weathered to iron oxides, giving them a characteristic rusty colour. This area of Gondwana was located adjacent to the Late Ordovician South Pole and both Anguiscolex africanus gen. et sp. nov. and Wronascolex superstes sp. nov. present a degree of polar gigantism, which has been suggested for other taxa in such high palaeolatitudes such as bryozoans, conulariids, trilobites and radiodonts. Lastly, the occurrence of Wronascolex extends the distribution of this typically Cambrian taxon into the Late Ordovician, indicating a total range for the genus exceeding 60 million years, more than any other palaeoscolecid genus described to date. urn:lsid:zoobank.org:pub:6FD5F086-FBC6-465C-B5B7-D29EF9A6B8FB. We are grateful to two anonymous referees for their detailed and constructive reviews. This work has been supported by the Spanish Ministry of Science and Innovation project CGL2017-87631-P and PDI2021-125585NB-10 (to JCGM) and by the Australian Research Council’s FT130101329 (to DCGB). This is also a scientific contribution to project IGCP 735 (IUGS-UNESCO). Julio Martín Sánchez (Collado Mediano, Madrid) and Julio Cabo Tapia (Navas de Estena, Ciudad Real) are thanked by their field assistance. Carlos Alonso (Complutense University of Madrid) is thanked for the photography of specimens. SEM photography and EDX analyses ...